Klâsik Türk şiirinde tevhîd (başlangıçtan XVI. asrın sonuna kadar) - Akpınar, İsa (My University, 2017)
Klâsik Türk şiiri sahasında kaleme alınan tevhîdlerin tespît ve değerlendirilmesini esâs alan bu çalışma, giriş ve dört bölümden oluşmaktadır. Tezin giriş bölümünde, İslâm düşüncesi ve edebiyatta tevhîdin mâhiyet, tarîf ve tahdîdi üzerinde durulmuştur.

The study, which bases on the determination and the evaluation of the “tevhîds” that written on the field of the Classical Turkish Poetry, consists of entry and four section. For the entry, Islamic thoughts and the origin of “tevhîd” in the literature are discoursed.
Keywords: Şiir; tawhid; tevhid poetry; Türk edebiyatı; XVI.yy